Analisis Seni Muqabalah Dan Implikasinya Terhadap Makna Al-Qur’an Surah Al-Mulk - Elpi Dayanti Siregar; Yarsha Ardhana Harahap (Yayasan Salam Cerdas Al-Fattah, 2025)
This study aims to examine the use of muqabalah as a rhetorical device in Surah Al-Mulk, specifically in verses 2, 15, and 20. Employing a qualitative methodology, the research conducts an in-depth analysis of these verses to explore the rhetorical contrasts embedded within the text, such as life and death, courage and fear, and success and failure. The study integrates classical and contemporary tafsir literature alongside rhetorical analysis to uncover how muqabalah functions not only to enhance semantic depth but also to intensify reader engagement and comprehension. The findings identify three distinct forms of muqabalah: muqabalah khilāfīyah in verse 2, muqabalah naẓīriyyah in verse 15, and muqabalah naqīḍiyyah in verse 20. These rhetorical contrasts serve as powerful devices that reinforce theological and moral teachings, heightening spiritual awareness and ethical responsibility. Moreover, the study emphasizes the pedagogical relevance of muqabalah in contemporary Qur’anic instruction, proposing its application as a tool to foster critical reflection and spiritual consciousness among learners. This research contributes to Qur’anic studies by highlighting the exegetical and educational significance of rhetorical devices in the Qur’an, and by offering innovative insights into how classical Arabic rhetoric can be contextually integrated into modern Islamic education.